Landmarks for Identifying the Suprascapular Foramen Anteriorly: Application to Anterior Neurotization and Decompressive Procedures. Issue 2 (3rd May 2017) - Manouvakhova, Olga V; Macchi, Veronica; Fries, Fabian N; Loukas, Marios; De Caro, Raffaele; Oskouian, Rod J; Spinner, Robert J; Tubbs, R Shane
Abstract: BACKGROUND: Additional landmarks for identifying the suprascapular nerve at its entrance into the suprascapular foramen from an anterior approach would be useful to the surgeon. OBJECTIVE: To identify landmarks for the identification of this hidden site within an anterior approach. METHODS: In 8 adult cadavers (16 sides), lines were used to connect the superior angle of the scapula, the acromion, and the coracoid process tip thus creating an anatomic triangle. The suprascapular nerve's entrance into the suprascapular foramen was documented regarding its position within this anatomical triangle. Depths from the skin surface and specifically from the medial-most point of the clavicular attachment of the trapezius to the suprascapular nerve's entrance into the suprascapular foramen were measured using calipers and a ruler. The clavicle was then fractured and retracted superiorly to verify the position of the nerve's entrance into the suprascapular foramen. RESULTS: From the trapezius, the nerve's entrance into the foramen was 3 to 4.2 cm deep (mean, 3.5 cm). The mean distance from the tip of the corocoid process to the suprascapular foramen was 3.8 cm. The angle best used to approach the suprascapular foramen from the surface was 15° to 20°. CONCLUSION: Based on our study, an anterior suprascapular approach to the suprascapular nerve as it enters the suprascapular foramen can identify the most medial fibers of the trapezius attachment onto the clavicle and insert a finger at an angle of 15° to 20° laterally and advanced to an average depth of 3.5 cm.